2021
DOI: 10.3390/antiox11010014
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Skin Carotenoid Levels and Metabolic Syndrome

Abstract: Carotenoids have potential antioxidant and anti-inflammatory effects; their protective roles are of particular interest in the pathogenesis of metabolic syndrome (MetS). The reflection spectroscopy method has been recently developed to noninvasively measure skin carotenoid (SC) levels, which highly correlates with serum concentration of carotenoids. The relationship between SC levels and metabolic syndrome has been investigated. We aimed to identify the differences in patient characteristics and SC levels betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
3
9
0
Order By: Relevance
“…The study did not find a difference in Veggie scores among the control, NDR, and DR groups, whereas female sex, nonsmoking status, and better BCVA were associated with higher Veggie scores (Table 10). Higher carotenoid levels in women and nonsmoking status have been reported previously [19][20][21]. Higher dietary intake of carotenoids in women than men has also been reported [22]; thus, the current results are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The study did not find a difference in Veggie scores among the control, NDR, and DR groups, whereas female sex, nonsmoking status, and better BCVA were associated with higher Veggie scores (Table 10). Higher carotenoid levels in women and nonsmoking status have been reported previously [19][20][21]. Higher dietary intake of carotenoids in women than men has also been reported [22]; thus, the current results are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Provitamin A carotenoids, which are converted into vitamin A, are essential for maintaining the photoreceptor cell function. Macular pigment xanthophylls, such as lutein and zeaxanthin, are the major protectants of the foveal region via their antiphotooxidative stress effects [ 19 ]. Filtering of the harmful shorter wavelength blue light and/or elimination of singlet oxygen species explains the cellular protection activities of these macular pigment carotenoids [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have shown an association between a diet that is rich in carotenoids, e.g., fruit and vegetables, and the risk of developing certain types of cancer according to the following principle: the more carotenoids in a diet, the lower the probability of cancer development [ 209 , 210 , 211 ]. The same relationship has been observed between a carotenoid-rich diet and the risk of cardiovascular [ 212 , 213 ], eye [ 214 ], and other diseases [ 11 , 215 ]. The inverse relationship for the development of lung cancer has been reported for heavy smoking individuals after supplementation of a high single dose of ß-carotene, which strongly exceeds the physiological concentration [ 68 ].…”
Section: Factors Resulting In the Reduction Of Carotenoids In The Scsupporting
confidence: 63%
“…The instrument can measure in the 350–850 nm range, which includes the absorption wavelengths of carotenoids around 480 nm. The association between skin melanin content and carotenoids is weakly correlated, indicating that SC levels are not affected by melanin absorption [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%